Volumetric Properties of Secondary Butanol and Tertiary Butanol in Water and Aqueous Micellar Systems of Sodium Dodecyl Sulphate (Journal of Scientific Research, 2020)
The apparent molal volumes of sec-butanol and t-butanol in water and in aqueous micellar system of sodium dodecyl sulphate have been determined from density measurements at different surfactant concentrations and temperatures. The partial molal volumes of the alcohols in aqueous micellar system at infinite dilution, V20 (mean, mic) were obtained from apparent molal volume data and compared with the corresponding values in aqueous solvent, V20  (mean, aq). The standard partial molal expansibilities, E20 (mean) of the alcohols were evaluated from V20 (mean) data at various temperatures. The transfer apparent molal volumes, ∆φtr0 for the alcohols from water to surfactant-water system are determined from apparent molal volume data. The sign and magnitude of these parameters are used to analyze the location of the solubilizate (alcohols) in the micellar system and the nature of interactions between alcohols and the micellar aggregates.